Analisis Penyebab Stagnansi ASEAN Defense Industrial Collaboration (ADIC) - Rayasti, Avelita Fitrianni; Anandi, Muhammad Fajar (Universitas Medan Area, 2024)
An independent defense capability is an aspiration and a crucial need for nations. Achieving this will ensure the state’s independence from the possible influence of weapon-producing states. To attain this goal, countries worldwide, including those in the ASEAN region, have endeavored to advance their weapon technologies through national defense industries. The ASEAN Defense Industrial Collaboration (ADIC), established in 2011, was conceived to emulate the success of European consortiums in producing diverse weapon technologies. Regrettably, after 11 years, ADIC has not produced or initiated the development of any weapon technology. The analysis in this article is conducted by synthesizing the perspectives of four key prerequisites for the success of defense industry cooperation: constructivist, institutionalist, liberal, and realist. The research method employed in this article is Causal Process Tracing (CPT), specifically aimed at identifying the prerequisites that lead to specific events. This article concludes that the failure of ADIC is attributed to five factors. Firstly, diverse economic systems among ADIC members create challenges. Secondly, equivalent defense industry capacities lead to competition and hinder collaboration. Thirdly, low spill-over effects from successful cooperation in other sectors impede progress. Fourthly, persistent distrust among ADIC member countries poses a barrier. Lastly, the absence of a defense alliance results in a strong consideration of relative gains. In essence, these factors underscore the complexity and challenges in achieving effective international defense collaboration.